THE DEVELOPMENT OF TRAINING CURRICULUM USING CHINESE COMMUNICATIVE APPROACH FOR PRIVATE SECTOR TOURISM BUSINESS OF ENTREPRENEUR IN NORTHERN BORDER CHIANGRAI PROVINCES - หวังตักวาดีน นิสรีน; ฉายจวิน หลิน (Chophayom Journal, 2018)
This research aimed to develop and evaluate the quality of training curriculum using Chinese communicative approach for private sector tourism business of entrepreneur in Northern border Chiang Rai province. The research methodology applied in this study was based on the Research and Development method which was divided into two phases: 1) the needs analysis of tourism business of entrepreneur, and 2) the development and evaluation of an effectiveness of training curriculum using Chinese communicative approach. The samples were 50 volunteers business of entrepreneur in Northern border Chiang Rai province. The research instruments used for collecting data were the developed training curriculum. The research results revealed that the developed training program reached the efficiency (E1/E2) at 83.50/87.00 which was in conformity with the established requirement of 80/80, and had the effectiveness index (E.I) of 0.68. Moreover, it was found that the business of entrepreneur participating in the training curriculum increased their knowledge and skills of using Chinese communicative approach for private sector tourism business before training curriculum implication at the .05 level of statistical significance. The developed training curriculum had a very large effect size (d=4.18) on their knowledge and skills. Furthermore, they increased their self-awareness toward using Chinese communicative before operation at the 0.05 level of statistical significance. The developed training curriculum had a very large effect size on their self- awareness (d=6.19). Finally, their satisfaction toward training curriculum in overall was found at the highest level ( =4.62). Keywords : training curriculum, Chinese, entrepreneur